THE PRINCIPLES OF TOLERANCE IN THE SCIENTIFIC HERITAGE OF IMAM MATURIDI - Ergashev Otabek Xasanovich (Bright Mind Publishing, 2026)
This article examines the life and scholarly-spiritual legacy of our compatriot, Imam Abu Mansur al-Maturidi, one of the most prominent representatives of the science of Kalam. The article highlights pedagogically the tolerance-based ideas of Maturidi’s teachings, which were founded by the scholar himself. Furthermore, the significance of Imam Maturidi’s works in countering various heterodox ideas is analyzed.
Keywords: Imam Maturidi, Ta’wilat Ahl al-Sunna, Maturidi school of Kalam, tolerance, refutations.